Building Primary School Teachers’ Capacity for Instructional Innovation through Academic Writing Mentorship: A Community Engagement Program in East Jakarta - Mohamad Syarif Sumantri; Laely Farokhah; Maisa Hurul Aeni; Wily Wandari; Venna Puspita Sari; Dessy Norma Juita (Indonesian Journal of Community Service in Education, 2026)
Primary school teachers possess classroom experiences, yet many require support in transforming them into publishable scholarly works. This community service program aimed to strengthen teachers’ scientific writing competence and encourage the development of a sustainable teacher-writer community at SDN Pondok Bambu 06, East Jakarta. The program was implemented through orientation, scientific writing workshops, individual and group mentoring, evaluation, and sustainability planning. Participants’ knowledge was evaluated using a 15-item pretest and posttest, supported by observations and reviews of their writing progress. The results indicated that participants demonstrated a high level of initial knowledge and maintained mastery after the program. The scope for measurable score gains was limited because baseline performance was already high, while pretest and posttest participation was not fully identical. The program provided a systematic foundation for identifying classroom problems, organizing academic ideas, and preparing scholarly manuscripts. Continued mentoring and portfolio-based assessment are recommended to strengthen sustainable writing practices.